Kinerja Penyuluh Pertanian Lapangan di Kecamatan Kotabunan Kabupaten Bolaang Mongondow Timur - Modeong, Chelsea Pradita; Ruauw, Eyverson; Benu, Noortje Marsellanie (Sam Ratulangi University, 2023)
This research aims to: 1). Knowing the internal factors and external factors agricultural field extension, 2). Knowing the performance of field agricultural extension in Kotabunan District, East Bolaang Mongondow Regency. This research was conducted from October to November 2022. The sampling method was purposive sampling. This research used primary data obtained through interviews and observation and secondary data obtained from books, previous research and BPS of Kotabunan District. The data obtained is presented in tabular form and then analyzed descriptively. Category determination is obtained based an assessment or score with the measurement method used is the Likert scale. The results of the study show that the internal factors that support are the extension workers are still in the productive age, some extension workers have a formal undergraduate education indicating that the human resources of the extension workers are quite good, most of the extension workers have enough years of work/work experience and all extension workers have attended training. The external factors that support the availability of sufficient facilities, infrastructure and information to make it easier for extension agents to carry out extension activities, good extension intensity can increase cooperative relations between farmers and a supportive reward system can increase enthusiasm and motivation for extension workers to work. The performance of field agricultural extension in Kotabunan District, East Bolaang Mongondow Regency is in the very good category. Performance indicators that show very good results include the preparation of extension programs, the availability of regional map data according to commodity zoning, the preparation of agricultural extension work plans in each work area, the dissemination of agricultural technology information evenly, and the growth and development of farmer empowerment and independence. The performance of extension agents that showed poor results was the realization of business partnerships between farmers and entrepreneurs and the realization of farmers' access to financial institutions.